2017
DOI: 10.1063/1.4998805
|View full text |Cite
|
Sign up to set email alerts
|

Tunable intersubband transitions in ZnO/ZnMgO multiple quantum wells in the mid infrared spectral range

Abstract: We report on controllable tuning of intersubband transitions in ZnO/Zn0.60Mg0.40O multiple quantum well structures grown by molecular beam epitaxy on sapphire. The transitions from the first to the second electronic energy state within the conduction band are directly observed by infrared spectroscopy. By variation of the quantum well width, the intersubband transition energies are tuned from 290 to 370 meV. The experimental results are in good agreement with theoretical calculations assuming the presence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…12 These intersubband photodetectors are tunable and unipolar devices. 13 So, they are used in devices in which bipolar doping is difficult to achieve. Therefore, this intersubband structure expands the choice of different materials for semiconductor photodetectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 These intersubband photodetectors are tunable and unipolar devices. 13 So, they are used in devices in which bipolar doping is difficult to achieve. Therefore, this intersubband structure expands the choice of different materials for semiconductor photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional MQW structures, such as GaAs/AlGaAs, have been extensively studied for the realization of IR photodetectors based on intersubband transitions 12 . These intersubband photodetectors are tunable and unipolar devices 13 . So, they are used in devices in which bipolar doping is difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is a wideband gap material with a band gap of 3.3 eV. Low dimensional structures of ZnO, together with its several alloys, such as ZnCdO, ZnMgO, and ZnBeO, have been studied (Ryu et al, 2006;Sadofev et al, 2007;Lange et al, 2011;Park et al, 2014;Pearton and Ren, 2014;Shtepliuk et al, 2015;Zhao et al, 2015;Orphal et al, 2017;Zúñiga-Pérez, 2017;Özgür et al, 2018;Liu et al, 2019;Sirkeli and Hartnagel, 2019;Yildirim, 2019;Pietrzyk et al, 2020;Park, 2020;Hong and Park, 2021;Meng et al, 2021;Yıldırım, 2021;Zhang, et al, 2022). It has been shown that ZnCdO/ZnO quantum wells are capable of emitting in the visible spectral range (Sadofev et al, 2007;Lange et al, 2011;Zúñiga-Pérez, 2017;Pietrzyk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent calculations on the intersubband transitions (ISBTs) in the ZnCdO/ZnO quantum wells show that these quantum wells yield in principle ISBT energies in THz and MIR ranges (Yildirim, 2019;Yıldırım, 2021). ZnO/ZnMgO quantum wells with a conduction band offset up to 0.7 eV offer ISBT energies reaching to the NIR region (Orphal et al, 2017). Recently, for instance, non-polar ZnO/ZnMgO quantum wells have been reported to have a THz electroluminescence (around 8.5 THz) based on intersubband transitions for the first time (Meng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Zinc oxide (ZnO) is a wide-band-gap semiconductor that can be used for transparent conductive layers, gas sensors, and optoelectronic devices. [7][8][9][10][11] One of the key techniques for fabricating ZnO-based devices is impurity doping to control the band gap and conduction type. 12,13) However, impurity incorporation and crystal growth rate are affected by the polarity of ZnO crystals.…”
Section: Introductionmentioning
confidence: 99%